GAJAH SEBAGAI SUMBER IDE PENCIPTAAN BENTUK RANCAKAN GAMELAN GADHON BERBILAH PAMOR - Sigit Pamungkas (Institut Seni Indonesia Surakarta, 2014)
Elephants are known as the most large-sized animals among the animals that live on land. With its large, forhumans are considered capable of representing the meaning of grandeur. This is evidenced by the many worksinspired by the elephant. In the creation of the artwork, the authors attempt stylized elephant shape in the form ofa set of rancakan gamelan gadhon, with the intention of adding value majesty of the gamelan instruments.Rancakan gamelan is part of the buffer strip, as well as a resonance tube that allows the blades gamelan aregenerally made of metal can cause a melodious voice. Rancakan form of gamelan gadhon the author createdcomes from the shape of elephants, with the intention to increase the strength of philosophical and aestheticquality is visually distinct from the common gamelan in the palace and in the community . Gamelan gadhon a termof simplifying the number of devices gamelan instruments with a practical purpose in mobility and performancegoals are simple tone composition. Generally gamelan gadhon meant to be played softly as accompanist anevent. Gamelan gadhon generally have five ricikan the form of gender, slenthem, kendang, gambang, and rebab.However, the author makes a set of gamelan gadhon consisting of: kendang ciblon, gender barung, gambang,slenthem, rebab, demung, saron, peking, and gongs kemodhong. It was intended for gamelan gadhon made tobe played more varied in character as well as working on the musical sound . Gamelan blades generally made ofiron, brass, or bronze . Each of the blade material will form its own tone shades. In this case, the authorsconducted an experiment to make blades gamelan using the prestige. Commonly found on the prestige of keris,spears, swords, blades and other traditional weapons. The prestige of a blend of iron and nickel through theprocess of forging and annealed complex. Making blades gamelan with prestige materials intended to add uniquevalue, so that a set of gamelan gadhon made into a unified work of creative and innovative, full of philosophicaland aesthetic values visually.Keywords: elephant, rancakan, gamelan, pamor